Association between health behaviors and depression: findings from the 2019 Brazilian National Health Survey - Marilisa Berti de Azevedo Barros; Lhais de Paula Barbosa Medina; Margareth Guimarães Lima; Renata Cruz Soares de Azevedo; Neuciani Ferreira da Silva Sousa; Deborah Carvalho Malta
ABSTRACT Objective: To analyze the association of depression with various health behaviors and to verify if they differ according to gender or income. Methods: This is a cross-sectional study based on data of 65,803 Brazilian adults (18-59 years old) interviewed in the National Health Survey, conducted in 2019. Presence or absence of depression was evaluated using the Patient Health Questionnaire (PHQ)-9. The prevalence of smoking, alcohol consumption, physical activity, sedentary lifestyle and food indicators were estimated according to the presence of depression. Stratified analyses were made according to sex and income, and prevalence ratios were estimated using the Poisson Regression. Results: We found a significant association between depression and all indicators studied, except occasional alcohol consumption. Depression was associated with heavy episodic drinking and insufficient consumption of fruits and vegetables only in women. In men, the associations of depression with sedentary lifestyle and with being a former smoker were stronger than in women. The occasional consumption of alcohol was more prevalent only in men without depression. The analysis stratified by income showed that the association of depression with physical inactivity is stronger in the higher-income group, while with heavy episodic drinking is only significant in the lower-income stratum. Conclusion: The results point to the need to consider mental health in programs aimed at reducing harmful health behaviors and the specificity of sociodemographic groups.